Cross-cultural pragmatics in e-commerce: a comparative study of buyer–seller interactions in Indonesia and Malaysia - Rohmadi (Indonesian Journal of Language and Communication Studies, 2026)
Background: E-commerce interactions are increasingly shaped by cross-cultural pragmatic differences, even between linguistically related markets such as Indonesia and Malaysia. Objective: This study aims to compare speech acts, politeness strategies, and conversational structures in buyer–seller interactions on Shopee Indonesia and Shopee Malaysia. Method: Using a qualitative comparative discourse analysis, 200 text-based exchanges (100 per country) were examined through Speech Act Theory and Politeness Theory. Results: The findings show that Indonesian sellers favor multi-act turns, directives, and positive-politeness strategies to promote immediacy and solidarity, while Malaysian sellers emphasize repair sequences, commissives, and negative-politeness strategies to ensure precision and professionalism. Additionally, code-switching patterns differ in frequency and function, and automated replies interact with cultural norms differently across contexts. These patterns reveal how platform affordances intersect with socio-cultural communication styles, shaping transactional efficiency and relational outcomes. Implication: The study’s implications highlight the need for culturally adaptive platform design and seller training to optimize customer engagement and trust in cross-border digital commerce. Novelty: This study contributes to comparatively demonstrating how culturally embedded pragmatic norms interact with platform affordances to shape distinct transactional discourse patterns in closely related e-commerce markets.